Progress in the synthesis of small-pore zeolites for purifying NOx from motor vehicle exhaust. (25th December 2022) - Yu, Qingjun; Cheng, Haodan; Tang, Xiaolong; Yi, Honghong; Ren, Xiaoning; Li, Zhenguo
Abstract: SSZ-13 and SSZ-39, as eight-member zeolites with small pore size of ∼0.38 nm, show profound development potential in eliminating NOx emitted from lean-burn vehicles. When were loaded with metal active components such as Pd/Co/Cu, they can be applied as PNAs or SCR catalysts due to their excellent NOx adsorption capacity/catalytic activity as well as superior hydrothermal stability. This work systematically reviewed the research progress of getting the pure SSZ-13 and SSZ-39 phases by both traditional hydrothermal synthesis method and the newly-developed trans-crystallization, seed-assisted as well as solvent-free synthesis method. Moreover, the incorporation of Pd and Cu into zeolites via the route of impregnation, ion exchange or one-step synthesis was also summarized. Simultaneously, the existence and distribution state of metal species in SSZ-13 and SSZ-39 zeolites according to different introducing methods were elaborated. In a word, by comparing the advantages and disadvantages of different methods for obtaining pure or the metal-modified SSZ-13, SSZ-39 zeolites, it is sincerely hoped this review could provide some guidance for the large-scale industrial application of these useful zeolites. Graphical abstract: Image 1 Highlights: Solvent-free route can reduce pollution, energy consumption, material loss and cost. The main way to obtain SSZ-39 is transcrystallization with FAU as parent zeolite. The main role of seed crystal is to provide surface on which target zeolite can grow. Pd species introduced into zeolites are mostly in the form of Pd 2+ and PdOx. Cu species is introduced mainly in the form of Cu 2+ ions.